Grammatical Errors in Using Adverbial Clauses of Reason as Modifiers in Some Indonesian Journalistic Headlines - Subagyo, Kukuh Prayitno; Chotib, Mochamad Nasrul; Widodo, Herditya Wahyu; Sujiatmoko, Ahmad Heki (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
This journal article examines the grammatical construction of some TV news headlines, highlighting the issues that arise due to their structure. The primary concern is that the headlines use adverbial clauses or phrases of reason before the main clauses which inadvertently cause some confusion about the subjects and the actions of the news stories. That is because the adverbial clauses or phrases often function as appositives to modify the subject of the main clause. When used as clauses of reason as in the headlines, this grammatical construction creates ambiguity in understanding who is then performing the described actions. The study finds that these headlines are structurally complex and misleading, making them fail to convey their intended meaning. To address this issue, the article suggests that the headlines be rephrased to eliminate ambiguity. Improved headline construction not only enhances communication but also ensures that potential confusion for the audience is minimized.